Importance of Tumour Suppressor Gene Methylation in Sinonasal Carcinomas - Chmelařová, M; Sirák, I; Mžik, M; Sieglová, K; Vošmiková, H; Dundr, P; Němejcová, K; Michálek, J; Vošmik, M; Palička, V; Laco, J (Folia biologica, 2016)
Epigenetic changes are considered to be a frequent event during tumour development. Hypermethylation of promoter CpG islands represents an alternative mechanism for inactivation of tumour suppressor genes, DNA repair genes, cell cycle regulators and transcription factors. The aim of this study was to investigate promoter methylation of specific genes in samples of sinonasal carcinoma by comparison with normal sinonasal tissue. To search for epigenetic events we used methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) to compare the methylation status of 64 tissue samples of sinonasal carcinomas with 19 control samples. We also compared the human papilloma virus (HPV) status with DNA methylation. Using a 20% cut-off for methylation, we observed significantly higher methylation in RASSF1, CDH13, ESR1 and TP73 genes in the sinonasal cancer group compared with the control group. HPV positivity was found in 15/64 (23.4 %) of all samples in the carcinoma group and in no sample in the control group. No correlation was found between DNA methylation and HPV status. In conclusion, our study showed that there are significant differences in promoter methylation in the RASSF1, ESR 1, TP73 and CDH13 genes between sinonasal carcinoma and normal sinonasal tissue, suggesting the importance of epigenetic changes in these genes in carcinogenesis of the sinonasal area. These findings could be used as prognostic factors and may have implications for future individualised therapies based on epigenetic changes.
Keywords: DNA-(cytosin-5-)methyltransferasa; Cadherins; Humans; kadheriny; Prognosis; DNA-(cytosin-5)-methyltransferasa 1; epigenomika; Papillomaviridae; Genes, Tumor Suppressor; dlaždicobuněčné karcinomy hlavy a krku; lidé; tumor supresorové geny; aktivace enzymů; DNA (Cytosine-5-)-Methyltransferase 1; Enzyme Activation; Carcinoma, Squamous Cell; prognóza; promotorové oblasti (genetika); Head and Neck Neoplasms; spinocelulární karcinom; Promoter Regions, Genetic; DNA Methylation; nádory hlavy a krku; Squamous Cell Carcinoma of Head and Neck; metylace DNA; Epigenomics; DNA (Cytosine-5-)-Methyltransferases